Urticaria mimickers in children. Issue 6 (November 2013) - Mathur, Anubhav N.; Mathes, Erin F.
Abstract Acute urticaria is a self‐limited cutaneous condition marked by transient, erythematous, and pruritic wheals. It is a hypersensitivity response that is often secondary to infection, medications, or food allergies in children. In contrast, the urticarial "mimickers" described in this review article are often seen in the context of fever and extracutaneous manifestations in pediatric patients. The differential diagnosis ranges from benign and self‐limited hypersensitivity responses to multisystem inflammatory diseases. Establishing the correct diagnosis of an urticarial rash in a pediatric patient is necessary to both prevent an unnecessary work up for self‐limited conditions and to appropriately recognize and evaluate multisystem inflammatory disorders. Herein, we describe two cases to illustrate the clinical manifestations, laboratory findings, histopathology and differential diagnoses for several mimickers of acute urticaria including: urticaria multiforme, serum sickness like reaction, Henoch‐Schönlein purpura, acute hemorrhagic edema of infancy, systemic onset juvenile idiopathic arthritis, cryopyrin associated periodic syndromes, and urticarial vasculitis.